Desain Simulator Sinar Matahari Guna Pengembangan Pendidikan dan Penelitian dibidang Photovoltaic System - , EVA SOFIAH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sunlight simulator for development of education and research in photovoltaic systems has been made of iron plate with a size (90 x 60 x 100) cm 3 are connecting it with an electronic circuit and test materials in the form of silicon photovoltaic modules mono crystal with size (35.5 x 25) cm2, and equipped with light sources of halogen lamps with specifications of 1000 W/220 V. In the field of education, the simulator has demonstrated a model of solar power plants, the concept of energy, energy conversion, temperature and heat, and electricity clearly, so that future simulator can be used as a medium of learning in high school and college level. While in the field of research, has been carried out measurements of silicon photovoltaic monokristal characteristic parameters in a state without irradiated and irradiated. In a state without irradiated, obtained parameters that RSH and Rs 16,667 respectively valued â¦ and 32.26 â¦. This parameter is largely determined by the quality of photovoltaic material. While in a state of halogen lamps illuminated perpendicularly with irradisi 993 W/m2, obtained parameters Isc and Voc-value 0.41 A and 18.92 V, the point of maximum power of 5.92 W, IMPP and VMPP respectively for 0, 39 A and 15.18 V. Based on these parameter values, the resulting value and efficiency of PV fiiling factor of 0.76 and 6.72. Of the three different measurements with irradiation, the resulting average value fiiling factor and efficiency silicon photovoltaic modules monokristal of 0.70 and 7.88%. Photovoltaic efficiency of this size are not good for monokristal silicon material. This shows the photovoltaic characteristics simulator gauges produced has not been good measurement accuracy caused by the temperature in the simulator exceeds the STC, but the future simulators can still be used for practical activities and student research related to the development of photovoltaic devices by taking into account the correction factor, ie by 1 , 6.